Função afim e suas propriedades através da resolução de problemas - Boschetto, Viviane Cristina [UNESP] (2015)
Learning difficulties with respect to mathematics has been growing in classrooms. This has motivated the search for teaching methods to motivate students and make the learning. In this paper we propose a didactic sequence to teach concepts related to function in order to use the problem-solving methodology and Geogebra computer program. This sequence was developed with students of the first grade of secondary school and the results presented. These concepts work by solving problems become the most autonomous student in training their knowledge and learning was verified by various resolutions of problems and active participation of them in the classroom. Experimentation with the use of technologies has made students generate conjectures and checked the results